Reduction of a dihydroboryl cation to a boryl anion and its air-stable, neutral hydroboryl radical through hydrogen shuttling. Issue 2 (29th November 2019) - Hagspiel, Stephan; Arrowsmith, Merle; Fantuzzi, Felipe; Hermann, Alexander; Paprocki, Valerie; Drescher, Regina; Krummenacher, Ivo; Braunschweig, Holger
Abstract : A doubly cyclic (alkyl)(amino)carbene-stabilised dihydroboronium cation undergoes fully reversible 2e − reduction to a stable hydroboryl anion via B-to-C hydrogen migration. Subsequent 1e − oxidation yields a bench-stable neutral hydroboryl radical. Abstract : The addition of Lewis bases to a cyclic (alkyl)(amino)carbene (CAAC)-supported dihydroboron triflate yields the mixed doubly base-stabilised dihydroboryl cations [(CAAC)BH2 L] + . Of these, [(CAAC)2 BH2 ]OTf (OTf = triflate) underwent facile two-electron reduction with KC8 owing to a 1, 2-hydride migration from boron to the carbene carbon to yield a stable hydroboryl anion. One-electron oxidation of the latter yielded the first neutral hydroboryl radical, which is bench-stable in the solid state.